Data Security and Service Overloading in Cloud Computing -An Overview - Prasad Vishwakarma, Ramesh; Tamrakar, Sitendra; Kumar Sharma, Rishi (International Journal of Computer Sciences and Engineering, 2025)
In the modern time of computing, Cloud computing will perform a major technical role in the IT world. Although various cloud service models are there present, Infrastructure as a Service (IAAS) has become the base of the next future Network of Services (NOS). Several advantages of cloud computing attracts the persons and organization to move their data from remote to the cloud. Cloud Providers mostly focus on providing services and provides a lesser focus on data security and privacy which is the main side of cloud computing. Since the single cloud storage does not fulfill the demands of the individuals and organizations, a move towards multi-cloud storage (MCS) has been emerged. In this report presents an overview of motivation of service overloading, attackers, different techniques and its limitations made to protect data security in the cloud storage .In this paper also explains the usual challenges in cloud storage services. This work delivers a superior solution in the service over loading architecture and key thought in the decision making process for the individuals and organizations in the adoption of superior cloud storage service.